Insertion water exchange increases right colon adenoma and hyperplastic polyp detection rates during withdrawal - Cadoni, Sergio; Falt, Přemysl; Sanna, Stefano; Argiolas, Mariangela; Fanari, Viviana; Gallittu, Paolo; Liggi, Mauro; Mura, Donatella; Porcedda, Maria L; Smajstrla, Vit; Erriu, Matteo; Leung, Felix W (Digestive and liver disease, 2016)
BACKGROUND: Single site studies in male Veterans in the U.S. reported increased detection of presumptive cancer precursors (adenomas, hyperplastic polyps) in the proximal colon (cecum-splenic flexure) by water exchange. AIMS: Assess the reproducibility of the observation. METHODS: Analysis of secondary outcomes collected prospectively in 3 similarly designed randomized controlled trials using water exchange, water immersion and insufflation (air or carbon dioxide). MAIN OUTCOME: detection rates of adenomas and hyperplastic polyps in proximal, transverse and right colon (cecum-ascending). RESULTS: 704 males (173 screening) were evaluated. In the proximal colon, WE showed increased detection of small adenomas (p=0.009) and adenomas plus hyperplastic polyps (p=0.015) (vs insufflation); increased detection of adenomas plus hyperplastic polyps of any size (p=0.045) and of small size (p=0.04) (vs water immersion). In the right colon water exchange increased detection of small adenomas (19% vs 12.1%, p=0.04) (vs insufflation); small adenomas (19% vs 12%, p=0.038), adenomas plus hyperplastic polyps of any size (25% vs 16.7%, p=0.028) and of small size (23.7% vs 14.6%, p=0.012) (vs water immersion). Water exchange significantly improved bowel cleanliness. Sedation had no impact on lesion detection. CONCLUSIONS: Water exchange is a superior insertion technique for detection of adenomas and hyperplastic polyps primarily in the right colon, especially those of small size.
Keywords: kolonoskopie; hyperplazie; logistické modely; Spojené státy americké; Humans; lidé středního věku; colon ascendens; Itálie; Aged; Cecum; Early Detection of Cancer; cékum; senioři; lidé; Hyperplasia; United States; reprodukovatelnost výsledků; časná detekce nádoru; Colonoscopy; Colonic Polyps; kolorektální nádory; Male; Reproducibility of Results; Middle Aged; voda; Czech Republic; Mass Screening; adenom; Adenoma; Water; plošný screening; Česká republika; mužské pohlaví; polypy tlustého střeva; Colon, Ascending; Italy; Logistic Models; Colorectal Neoplasms